Children's sleep and academic achievement: The moderating role of effortful control. (March 2017) - Diaz, Anjolii; Berger, Rebecca; Valiente, Carlos; Eisenberg, Nancy; VanSchyndel, Sarah K.; Tao, Chun; Spinrad, Tracy; Doane, Leah D.; Thompson, Marilyn S.; Silva, Kassondra M.; Southworth, Jody
Poor sleep is thought to interfere with children's learning and academic achievement (AA). However, existing research and theory indicate there are factors that may mitigate the academic risk associated with poor sleep. The purpose of this study was to examine the moderating role of children's effortful control (EC) on the relation between sleep and AA in young children. One hundred and three 4.5- to 7-year-olds (M = 5.98 years, SD = 0.61) wore a wrist-based actigraph for five continuous weekday nights. Teachers and coders reported on children's EC. EC was also assessed with a computer-based task at school. Additionally, we obtained a standardized measure of children's AA. There was a positive main effect of sleep efficiency to AA. Several relations between sleep and AA were moderated by EC and examination of the simple slopes indicated that the negative relation between sleep and AA was only significant at low levels of EC.